Book Lengths and Target Age Groups: Writing for Young People in Regions Outside the UK and US - Kristien Potgieter (Leaf Journal)
Most guidelines for writers for young people concerning book lengths and target age groups found online and taught in creative writing courses are, understandably, geared towards the UK and US markets. But for those authors who are based elsewhere and aim to write for their home market – as in my case, South Africa – categories such as picturebooks, Middle Grade fiction and Young Adult fiction will have different book lengths and target ages associated with them. In South Africa, for example, picturebooks are often read by children as old as eight and nine years old. This has clear implications for the author, who must try to keep the target age of the reader in mind when writing.